Simulation and analysis of wave-structure interactions for a semi-immersed horizontal cylinder. (1st January 2018) - Tan Loh, Teng; Pizer, David; Simmonds, Dave; Kyte, Adam; Greaves, Deborah
Abstract: The paper is concerned with the use of the open source computational fluid dynamics software package, OpenFOAM ® for predicting and analysing the behaviour of a semi-immersed horizontal cylinder subject to different types of wave conditions. This study involves two separate cases of wave-structure interaction involving a semi-immersed horizontal cylinder, which may represent the simplified form of a cylindrical component of a wave energy converter. First, the flow around a fixed semi-immersed horizontal cylinder subject to regular waves is studied, in which the horizontal and vertical forces are computed and compared to linear wave theory and available experimental data. Further, a semi-immersed horizontal cylinder with a prescribed oscillatory vertical motion is considered to determine the surface wave elevations generated by the motion of the cylinder. The measured numerical surface elevations are also compared with theoretical predictions and experimental data. Both cases considered in this paper are simulated in a numerical wave tank where wave relaxation zones are utilised to avoid wave reflections. It is concluded that the numerical data produced by OpenFOAM ® provide good overall agreement within the limitations of the relevant theory and experimental data. Highlights: Use of CFD for simulating a semi-immersed horizontal cylinder in a 2D NWT. Horizontal and vertical wave forces induced on a semi-immersed horizontal cylinder. Free surface waves generated by a cylinder through prescribed oscillatory motion. Validations by comparison with theoretical predictions and experimental data.